Synthesis of novel pyrroles and fused pyrroles as antifungal and antibacterial agents - Rania Helmy Abd El-Hameed; Amira Ibrahim Sayed; Shima Mahmoud Ali; Mohamed A. Mosa; Zainab M. Khoder; Samar Said Fatahala (Taylor & Francis Group, 2021)
Pyrroles and its fused forms possess antimicrobial activities, they can easily interact with biomolecules of living systems. A series of substituted pyrroles, and its fused pyrimidines and triazines forms have been synthesised, all newly synthesised compound structures were confirmed by spectroscopic analysis. Generally, the compounds inhibited growth of some important human pathogens, the best effect was given by: 2a, 3c, 4d on Gram-positive bacteria and was higher on yeast (C. albicans), by 5c on Gram-negative bacteria and by 5a then 3c on filamentous fungi (A. fumigatus and F. oxysporum). Such results present good antibacterial and antifungal potential candidates to help overcome the global problem of antibiotic resistance and opportunistic infections outbreak. Compound 3c gave the best anti-phytopathogenic effect at a 50-fold lower concentration than Kocide 2000, introducing a safe commercial candidate for agricultural use. The effect of the compounds on DNA was monitored to detect the mode of action.